The genus Emitrombidium Lombardini, 1949 (Actinotrichida: Trombidiidae) resurrected - Mąkol, Joanna; Sevsay, Sevgi (Zootaxa, 2014)
Emitrombidium giocondi sp. nov., a second species of Emitrombidium is described based on postlarval forms originating from Turkey. The history of the genus is retraced. The previous conjectures about the uncertain family affiliation of Emitrombidium are clarified and the genus is reinstated as a member of Trombidiidae. Hitherto records suggest the Mediterranean and Pontic distribution of the genus.